Education and social change : contours in the history of American schooling - Rury, John L., 1951- (Routledge, 2013)
"This brief, interpretive history of American schooling focuses on the evolving relationship between education and social change. Like its predecessors, this new edition investigates the impact of social forces such as industrialization, urbanization, immigration and cultural conflict on the development of schools and other educational institutions. It also examines the various ways that schools have contributed to social change, particularly in enhancing the status and accomplishments of certain social groups and not others. Detailed accounts of the experiences of women and minority groups in American history consider how their lives have been affected by education. Changes in this new edition include the following: A more thorough treatment of key concepts such as globalization, human capital, social capital, and cultural capital. Enhanced attention to issues of diversity throughout. Greater thematic coherence as a result of dividing chapter 6 into two chapters, the first focusing on the postwar period and emphasizing the themes of equity and social justice and the second focusing on human capital in education, highlighting the standards movement, federal policy changes and neo-liberal reform. A revision of several focal point discussions for greater clarity and thematic releance. Update discussions of recent changes in educational politics, finance and policy, especially the troubles presently facing No Child Left Behind (NCLB). "--